A Group of Physician’s Evaluation About the Turkish Penal Code Numbered 5237 Questionnaire Training - Odabaşı, Aysun Balseven; Tümer, Ali Rıza; Odabaşı, Orhan (The Bulletin of Legal Medicine, 2008)
Turkish Penal Code (TPC) Number of 5237, which has been in effect since June, 2005, has brought forward some new arrangements in medical practice, as it has in all areas of society. The aim of this study is to evaluate the level of knowledge among the medical practitioners and a group of physician specialists on the articles of Turkish Penal Code concerning the medical practice and their opinions on some controversial articles. Between May 17, 2005 and November 20, 2005 a survey based on 13 questions about the modifications of Turkish Penal Code has been done on 429 specialists and practitioners and the data was evaluated by SPSS 11.0 software. 25,9% of the physicians were 26-30 years old, 24,5% of them were 31-35 and 22,6% of them at the age of 36-40 who have provided answers to the questions. Ill participants (25,9% of the group) have been physicians for 1-5 years. 76,9% of the physicians were specialists, 19,3% of them were practitioners. 80,9% of the physicians said “NO” in answer to the question “Have you got education on the Turkish Penal Code Numbered 5237”. 69% of the physicians said in their answers to the question concerning the informing responsibility of physicians that they will inform the authorities when they find an indication that a crime might have been committed by a patient. The results of the survey stated that the physicians do not have adequate information about TPC Numbered of 5237. First of all, the physicians must be informed about recent TPC and their legal responsibilities, the articles of the code which may cause serious problems in medical practice must be discussed. How the article concerning the informing responsibility of the physicians may cause problems in practice must be taken into consideration. Key words: Turkish Penal Code, legal responsibilities, physicians